Building Collective Identity: A Study of the Narrative of Housing Justice in Zohran Mamdani's Digital Campaign - Sheila Merista (Penerbit Jurnal Indonesia, 2026)
This article analyzes how Zohran Mamdani's digital campaign on @ZohranforNYC YouTube channel builds a politicized collective identity among the working class and renters in New York City through narratives of housing crisis and economic justice. This study uses a qualitative approach with content analysis of several campaign videos that were purposively selected because they are considered the most powerful and representative in displaying the issues of high rents, structural inequality, and working-class solidarity. The theoretical framework of Politicized Collective Identity (PCI) from Bernd Simon and Bert Klandermans is used to read how these contents construct three main processes of identity politicization, namely: (1) collective awareness of injustice through the exploration of the experience of the housing crisis as a collective grievance; (2) attribution to the opposite party by positioning the political elite, corporate landlords, and housing policy structures as a source of suffering; and (3) community involvement (triangulation) through visual volunteer mobilization, door-to-door action, and cross-community support that makes housing issues a public interest throughout the city. The study aims to explain how digital political communication can transform scattered everyday complaints into a coherent collective narrative that encourages solidarity and political action. The findings show that the combination of personal narratives, visual symbols of the working class, and inclusive emotional language makes Zohran's YouTube channel not only an electoral campaign space, but also an arena for the formation of collective identities that drive political participation and structural change. The article concludes that politicized collective identity, when articulated through digital media, can become an effective strategy to strengthen the voice of marginalized groups and to reframe local housing crises as moral and political issues that must be addressed collectively.